2013
DOI: 10.1007/s10815-013-9982-4
|View full text |Cite
|
Sign up to set email alerts
|

Polar body fragmentation in IVM oocytes is associated with impaired fertilization and embryo development

Abstract: Fragmented polar bodies likely reflect cytoplasmic incompetence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
12
0
4
Order By: Relevance
“…Morphologic variations of the oocyte observed in IVF cycles may result from intrinsic factors, such as age and genetic defects, or extrinsic factors, such as COH protocol and ovarian response to COH. The occurrence of specific cytoplasmic dysmorphic phenotypes in oocytes has been suggested to reflect intrinsic defects that may negatively influence oocyte competence [11,34,35]. The NPVS/HZP oocytes collected in this study were specific abnormal oocytes found in our IVF lab, which maybe originated from oocytes development defects.…”
Section: Discussionmentioning
confidence: 73%
“…Morphologic variations of the oocyte observed in IVF cycles may result from intrinsic factors, such as age and genetic defects, or extrinsic factors, such as COH protocol and ovarian response to COH. The occurrence of specific cytoplasmic dysmorphic phenotypes in oocytes has been suggested to reflect intrinsic defects that may negatively influence oocyte competence [11,34,35]. The NPVS/HZP oocytes collected in this study were specific abnormal oocytes found in our IVF lab, which maybe originated from oocytes development defects.…”
Section: Discussionmentioning
confidence: 73%
“…Anormal PB ve perivitellin aralık, sitoplazmik vakuol-granül varlığı gibi dismorfizmlerin IVF üzerine etkisini anlayabilmek için birçok çalışma yapılmıştır. [9] Bu çalışmaların bir kısmı bu dismorfizmlerin fertilizasyon ve embriyoner gelişim üzerine olumsuz etkisi olduğunu bildirirken, [11][12][13] bir kısmı da etkisi olmadığını bildirmektedir. [14,15] Çalışma-mızda 39 yaş üstü kadın bulunmamakta ve yapılan bir çalışmada 45 yaş ve üstü kadınlarda ZP kalınlaşması-nın ister klasik IVF ister ICSI uygulansın, fertilizasyonu negatif etkilemediği bildirilmiştir.…”
Section: Discussionunclassified
“…[9] Çalışmamızda PB büyüklüğü ile fertilizasyon arasında bir bağlantı gözlemedik. Oosit sitoplazmik granülaritesi hasta yaşı ve stimülasyon protokolünden etkilense de, fertilizasyona ve embriyonik gelişime etki etmediği ama refraktil cisim varlı-ğında klivaj oranının düştüğü ve embriyonik gelişimin bozulduğu bildirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Later, Ebner et al [93] confirmed the relationship between PB1 morphology, fertilization and blastocyst quality, but also a positive effect on implantation and pregnancy rates. Similarly, Rose et al [96] reported that oocytes with an intact first PB have high fertilization rates and better embryonic development, whereas those displaying a PB1 of large size, irregular shape, rough surface or fragmentation are less competent after IVF, yielding low pregnancy rates after embryo transfer. In contrast, others have not reported any correlation [97][98][99].…”
Section: First Polar Body Assessmentmentioning
confidence: 94%